Implementasi Lisensi Wajib TRIPs Agreement Dalam Produk Pharmasi Di Australia - Muhammad Naufal Murtadho (Journal Law and Government, 2025)
This study aims to analyze the implementation of compulsory licenses as per Article 31 of the TRIPS Agreement in the context of pharmaceutical products in Australia. Compulsory licenses provide flexibility to WTO member countries to produce or use patented medicines during public health emergencies. Under Australia's Patents Act 1990, Section 133 provides for the grant of compulsory licenses that allow the exploitation of patents without the consent of the rights holder, provided that reasonable compensation is provided. This study uses a qualitative approach with normative legal research methods to examine the regulation and application of compulsory licenses in Australia. The analysis is conducted through a review of legislation, legal literature, and a case study of the H1N1 vaccine produced by CSL Limited during the 2009 pandemic. The results show that the compulsory license mechanism in Australia has been designed to comply with the TRIPS Agreement and ensure a balance between the interests of patent holders and public health needs. The obstacles faced by Indonesia in accessing vaccines are more due to global supply issues and high demand than Australia's violation of Article 31 TRIPS. This research confirms the importance of compulsory licenses in the face of the global health crisis. A fair and effective implementation of compulsory licenses can improve access to essential medicines, support public health, and fulfill the principles of fairness in licensing.